Experimental determination of flow patterns and water holdup of low viscosity oil-water system in horizontal pipes - Onuoha, M.D.U.; I. Ismail,; A.S. Ismail,; M.F. Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Fluids with different properties would exhibit different flow behaviour in any multiphase flow system at a given operating condition. Therefore, an in-depth knowledge of the operational and flow behaviour of any known fluid properties in a multiphase flow system of either liquid-liquid two-phase flow (oil and water) or gas-liquid-liquid three-phase flow (gas, oil and water) would be helpful in designing of pipelines and optimization of the production, separation, transportation and distribution systems, as may be found in oil and gas and allied petro-chemical industries. This paper presents the experimental observation of the flow patterns and water holdup for a two-phase low viscosity oil-water flow in horizontal pipes. The test fluids comprised of tap water and 2D-diesel which has a density of 832 kg/m3, viscosity of 3.24 mPa.s, surface tension of 0.030 N/m and flash point of 79°C. A total of 30 runs has been accomplished and the experimental results showed three different flow patterns identified as stratified flow (ST), stratified flow with mixing interface (ST&MI) and water-in-oil dispersed flow (), with superficial velocities of oil and water in the ranges of 0.32 - 0.87 m/s (Vos) and 0.20 - 0.90 m/s (Vws), respectively. However, analysis of water holdup in the commingled flows of the test fluids showed its dependency on the fluid flow patterns and superficial velocity of water.